Polarized optical properties of a GaInP lateral superlattice - Min, KI; Lim, JR; Kim, JS; Rho, H; Hahn, JR; Song, JD; Choi, WJ; Kim, JM; Lee, YT (KOREAN PHYSICAL SOC, 2006)
We report the optical properties of (GaP)(1)/(InP)(1) short-period superlattice (SPS) structures in the presence of lateral composition modulation (LCM). LCM is related to alternating Ga-rich and In-rich GaInP bands elongated along the [110] direction. Polarized photoluminescence (PL) measurements exhibit a strong anisotropy in the presence of LCM. Polarization anisotropy in a PL response is not observed for a, sample in which no LGM forms. Raman spectra taken from the top surface of the sample exhibit a GaP-like longitudinal optical (LO) phonon response at 383 cm(-1) all InP-like LO phonon response at 363 cm-1, and a. transverse optical (TO) phonon response at 330 cm-1. The LO-like and the TO-like characteristics of these phonon modes axe further investigated by taking Raman spectra, from the cleaved edge of the sample in various polarization configurations.
Keywords: COMPOSITION MODULATION